مدى توافر كفايات التدريس الفعال في عملية التعليم عن بعد لدى المعلمين في لواء البتراء من وجهة نظرهم - الهلالي، الهام جهاد إبراهيم (جامعة جرش, 2022)
هدفت هذه الدراسة إلى الكشف عن مدى توافر كفايات التدريس الفعال في عملية التعليم عن بعد لدى المعلمين في لواء البتراء من وجهة نظرهم، ولتحقيق ذلك طورت الباحثة استبانة مكونة من (42) فقرة، وتم التحقق من صدقها، ودرجة ثباتها والتي بلغت (0.91%). تكونت عينة الدراسة من (200) معلم ومعلمة، وقد استخدم المنهج الوصفي المسحي من أجل تحقيق أهداف الدراسة، وللإجابة عن أسئلة الدراسة استخرجت المتوسطات الحسابية والانحرافات المعيارية وتحليل التباين الأحادي واختبار شيفيه. وأظهرت النتائج أن تقديرات المعلمين الأكثر أهمية لمدى توافر كفايات التدريس الفعال في عملية التعليم عن بعد كانت: توظيف التطبيقات الحديثة، واستخدام أدوات التكنولوجيا، بينما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية تعزى لمتغير النوع الاجتماعي والمؤهل العلمي، ووجود فروق ذات دلالة إحصائية تعزى لمتغير الخبرة العملية لصالح فئة أكثر من (15) سنة في مجال توظيف التطبيقات الحديثة. وأوصت الدراسة بضرورة تقديم دورات تدريبية دورية للمعلمين والمعلمات بعنوان التعلم الإلكتروني وكيفية توظيفها في المواقف التعليمية، وتشجيع المعلمين والمعلمات التقدم للدورات التدريبية المتقدمة في مجال توظيف التطبيقات الحديثة في عملية التعليم. This study aimed to detect the extent of availability of the effective teaching competencies for the distance learning of teachers in the District of Petra from their point of views. The researcher designed questionnaire consisting of (42) items. It was tested for reliability at (0.91%). The questionnaire was distributed to (200) male and female teachers in which the descriptive scanning approach has been used to achieve the objectives of the study. For data analysis, means, standard deviations, the use of contrast uni-analysis and Scheffe test. The results showed that the most important teacher’s estimates to the extent of availability of the effective teaching competencies for the distance learning of teachers in the District of Petra were: Applying the new teaching methods, use the technology tools. It also showed no statistical significant differences among study area attributed to gender and educational qualification. The statistical significant differences found were attributed to teaching experience in favor to the teaching experience (which exceeds 15 years) in the field of technology tools. The study recommends organizing workshops for the teachers about e learning and how to apply it in educational situations. Encouraging teachers to apply for advanced training courses in the field of applying the modern applications in the education process.
Keywords: التعليم الإلكتروني -- الكفايات التدريسية -- أعضاء هيئة التدريس -- السياسات التعليمية -- الأردن